2017
DOI: 10.1002/pc.24689
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, dielectric, tunable electromagnetic interference shielding and thermal characteristics of multiwalled carbon nanotube incorporated polymer nanocomposites: A facile, environmentally benign and cost effective approach realized via polymer latex/waterborne polymer as matrix

Abstract: Recent years have witnessed an increased interest in the designing of composite materials in an uncomplicated and economical route for electromagnetic interference (EMI) shielding applications. Herein we report a simple; user friendly and cost effective method comprising of aqueous emulsion of polypropylene (PP) being used as the polymer matrix to manufacture uniformly and efficiently dispersed multiwalled carbon nanotube (MWCNT) incorporated PP composites with excellent electrical conductivity and EMI shieldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
(124 reference statements)
1
5
0
Order By: Relevance
“…This indicated that the nanocomposites exhibited almost similar EMI-SE in both the X-band and K u -band and there is a negligible variation with varying frequency. This is similar to the results reported by George et al [67] for the polypropylene (PP)/MWCNT nanocomposites prepared by the solution method followed by hot pressing. However, in contrast to the PES/MWCNT (which showed 29-30 dB) nanocomposites, the PP/MWCNT showed a total EMI-SE of about 25 dB for the 10 wt% MWCNT nanocomposite.…”
Section: Electromagnetic Interference-shielding Effectiveness (Emi-se)supporting
confidence: 91%
See 1 more Smart Citation
“…This indicated that the nanocomposites exhibited almost similar EMI-SE in both the X-band and K u -band and there is a negligible variation with varying frequency. This is similar to the results reported by George et al [67] for the polypropylene (PP)/MWCNT nanocomposites prepared by the solution method followed by hot pressing. However, in contrast to the PES/MWCNT (which showed 29-30 dB) nanocomposites, the PP/MWCNT showed a total EMI-SE of about 25 dB for the 10 wt% MWCNT nanocomposite.…”
Section: Electromagnetic Interference-shielding Effectiveness (Emi-se)supporting
confidence: 91%
“…Abbas et al [27] reported an EMI-SE of 35 dB (in the X-band) for 20 wt% MWCNT filled Poly(ether-sulfone) (PES) nanocomposites (thickness = 0.5 mm) fabricated by the solution method. Similarly, George et al [28] reported an EMI-SE of ∼47 dB (in the X-band) for the 2 mm thick PP/MWCNT composite fabricated by the solution method followed by hot pressing. The functionalization of the CNTs can also increase the EMI-SE compared to CNTs without functionalization.…”
Section: Introductionmentioning
confidence: 78%
“…In order to further illustrate the utility and advancement of in‐situ synthesized rGO/mC‐A, the comparison of the dielectric constants and EMI SE performance of our results and previously reported values are shown in Figure 5. As a result, Figure 5E, F demonstrate the superiority of in‐situ synthesized rGO/mC‐A with in terms of relatively high dielectric constants and EMI SE values at low addition of rGO, compared to other systems, such as CNT/Epoxy, [ 40 ] MWCNTs/Epoxy, [ 41 ] MWCNT/PS, [ 42 ] MWCNT/PP, [ 43 ] TGO/SCI/Epoxy, [ 44 ] Graphene/Epoxy, [ 45 ] GNPs/Epoxy, [ 46 ] rGM/Epoxy, [ 47 ] GNPs/Epoxy, [ 48 ] Graphene/PU, [ 49 ] Graphene/TPU, [ 50 ] at 8.2–12.4 GHz.…”
Section: Resultsmentioning
confidence: 97%
“…An important problem in the synthesis scheme of PCCCM considered above is to ensure close interaction of the modifying additive nanoparticles with the initial polyvinyl chloride molecules (or aggregates of molecules). This problem is of interest, per se; it is considered in many studies where PVC modification by carbon NC is used to render antistatic or shielding properties to NC/PVC composite materials [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], to improve thermal or electrophysical properties [ 39 , 40 , 41 , 42 , 43 , 44 ], and to apply such materials in energy storage devices [ 41 , 42 ], chemical sensors [ 41 , 42 ] and microelectronics [ 39 , 44 ]. A uniform distribution of carbon nanoparticles in PVC melt or its solutions in organic solvents is obtained using ultrasonic treatment [ 33 , 40 , 41 , 42 , 44 , 45 ], preliminary surface functionalization of the modifying carbon nanoparticles [ 46 , 47 , 48 ], surfactant additives [ 49 , 50 ], and mechanical mixing in a dry form in special-purpose mills [ 35 , 39 , 42 , 43 ] or extruders [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%